White matter changes in thalamic stroke [Talamik ̄nmede ak madde deʇişimleri] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2003)
Stroke as one the most significant health problems can be diagnosed by clinical symptoms and medical imaging modalities. Stroke patients mostly suffer from white matter changes, so the detection of any change in the white matter is important in that the white matter is directly affecting the brain functions. Diffusion tensor imaging, which allows the determination of the microstructural properties of white matter noninvasively yields to extract the tissue changes due to pathology. This study focuses on the brain areas of patients affected by thalamic stroke using the brain fiber tracts' distribution which allows the quantitative tracking of white matter changes. Besides the comparison of the stroke patients with the healthy control group, variations in white matter volume and the fiber tract distribution between the right and left thalamic stroke cases are also computed in a voxel-wise manner. The statistical analyses result that in thalamic stroke patients, the total number of voxels with white matter and the total volume of white matter have been decreased with respect to controls. The developed spatial masks aid to investigate the structural properties of the stroke whether it's in the right or left side of thalamus. Results allow one to discuss the voxel statistics of thalamic stroke cases and subjectwise comparison of the same fibers. © 2014 IEEE.